Effects of Maharishi Amrit Kalash 5 as an Ayurvedic herbal food supplement on immune functions in aged mice - Sugiura Haruo; Mirbod Seyed; Inaba Ryoichi (BMC, 2005)
Abstract Background Maharishi Amrit Kalash (MAK) 5, one of the Ayurvedic food supplements, belongs to a group of substances known as Rasayana. MAK5 and other Rasayanas are believed to enhance the body's resistance to infections and disease, and enhance longevity. In this study, we determined the effects of administration of MAK5, one of the Ayurvedic food supplements on immune functions in young and old mice. Methods Male C3H/He N mice were divided into five groups: two no treatment groups (old control: 22-month-old and young control: 2-month-old) and three MAK5 treated groups with differing dose of MAK5. MAK5 was given p.o. at 50 mg/kg, 100 mg/kg or 200 mg/kg per day (3 days/week) for 2 months. Results We found that glucose consumption of peritoneal macrophages from old mice treated with MAK5 at all doses and incubated for 48 and 72 h were significantly greater than that in the control group. Nitric oxide production of peritoneal macrophages stimulated by lipopolysaccharide (LPS) in old mice treated with MAK5 at all doses was significantly greater than that in the old control group, but not compared to the young control group. Stimulation index (S.I.) in old mice gavaged with MAK5 at all doses was significantly higher than that in the old control group. IL-2 production stimulated by Con A in old mice given MAK5 at all doses was significantly higher than that in the old control group. Production of IFN-γ stimulated by Con A in old mice given MAK5 at doses of 100 mg/kg and 200 mg/kg were significantly higher than that in the old control group. IL-4 production of splenic lymphocyte stimulated by Con A in old mice given MAK5 at dose levels of 100 and 200 mg/kg were significantly higher than that in the old control group. Conclusion The results suggest that MAK5 suppressed the age associated glucose consumption of peritoneal macrophages and cellular immune function reduction, and that it contributes to the prevention of the immunosenescence.